Catalisadores de nióbio com propriedades anfifílica empregados no estudo de transformação de biomassa - Talita Evelyn de Souza (2017)
In this work, new catalysts based on niobium oxalate ammonium(NH4[NbO(C2O4)2(H2O)](H2O)n), niobium chloride (NbCl5) and niobium oxide (Nb2O5.nH2O) as precursor, were synthesized and characterized by controlled precipitation and hydrothermal synthesis. Amphiphilic catalysts were also synthesized in the presence of CTAB (cetyl trimethylammonium bromide), to apply in byphasic systems as glycerol:acetone on acetalization reactions, wich is the target in this work. Catalysts obtained by niobium oxalate ammonium, showed high acidity such as Nb2O5.nH2O, it decreases about 31 % by hydrophobization process, however improves glycerols conversion of 41 to 65%. Catalysts obtained by NbCl5, showed lower acidty than the other catalysts, but showed high BET specific area like 198 m2g-1 and presence of mesoporous, with good glycerol conversion results. In the same way, catalysts obtained by hydrothermal synthesis, showed high BET are, next to 192 m2g-1 and mesoporous structure. Differents niobium precursors and surfactant incorporation in the synthesis of the catalysts can exhibit different morphology, BET specific area and acidity. These properties act in the same time making a synergism and improve catalytic activities, mainly in biomass conversion reactions using biphasic systems.